Entre o corredor e a estância: dinâmicas sociais e produtivas na APA do Rio Ibirapuitã - Brito, Andréia Nunes Sá (2010)
The creation of APAs, as other direct-use units of conservation, come from the current demand of linking the preservation of natural patrimonies and historic-cultural in the territories. However, the lack of participation by the local community on the decision-making processes contradicts this possibility. At the RiO Ibirapuita‟s APA, site of this study, this same conflict occurs, due to the lack of adequate knowledge on the farmers‟ characteristics and management practices. In order to cease such deficiency, this study aims to characterize the limits and main dynamics, which were evidenced among the typical Pampa‟s social groups at the Rio Ibirapuita‟s APA. To approach that, based on progressive steps, the Analysis and Diagnosis of the Agrarian Systems was used as the main reference. The initial information collected was based on agroecological characterization and socio-economic aspects of the region, as well as, field surveys for the establishment of pre-typology. The assessed groups were submitted to semi-structured surveys, participative observations and, the use a field logbook. For the data analyses, it was used the Aggregated Value theory, multivariate statistical analysis and, speech analysis. The results highlighted for the Pampa region, the rural characteristic related to the human groups that inhabit that region, since pre-historical times. Thus, with the social-economic profile linked to the beef cattle farming activity and to the territorial disputes, the agrarian structure is based on the large sized rural estates. Through the APA‟s agroecologic characterization, three homogeneous zones were identified, in all of them, the beef cattle farming activity predominated. In the first zone, the one located at the highest altitude and in the southern part, the beef cattle farming activity is hegemonic; in the second zone, in the southwestern part of the region and located at middle altitude, the cattle farming activity shares land with dryland cereal cultivation and; in the third zone, in the northern part and at the lowest altitudes, the cattle farming activity occurs concomitantly with the flooding rice fields by the river shore. The demographic distribution follows the logic of these regions, in one way by being characterized by the large sized farms, and in another, by being dominated by the logical family, which clumps the dwellings and the Rincoes. In the large sized farms we found farmers of the employer segment, divided between business and traditional and / or tourism. In the Rincoes, the farmers of the Family segment are from Estancieira origin, they are also changueiros Employees, Retirees, Quilombo, Merchants, or Occupiers and aggregates. Passing in the hallways, between these two extremes, is the segment of the proletariat, composed by temporary and permanent employees and also by the walkers or teatinos. The types of production systems predominantly practiced in these establishments include beef cattle farming, subdivided into combinations of cattle and grain, cattle and sheep, cattle, sheep and "crops inside fences," and rice. It is possible to point out the relationship between work, gender and the environment. In addition, it is addressed their unique strategies, of the "cattle corridor", rental of animals "per head", the joint sales, tourism and environmental marketing. It appears under this scenario the need to recognize and act to mediate these relationships in order to reduce the discrepancies between social groups, and enjoy the traditional knowledge towards the conservation of agricultural ecosystems and cultural heritage present in the Pampa Biome.